Collaborative Governance Pentahelix Model in Building Commerce Institutions for Coffee Agroforestry in West Java - Nadia, Yussi (KnE Social Sciences, 2022)
The challenge of implementing the Social Forestry Program is how to involve all stakeholders in the development of the three social forestry management areas, namely: institutional management, forest area management and business management. Doing so would enable the main objectives of the program to be achieved, specifically promoting the sustainability of the forests and prosperous communities. An initial survey was conducted which showed that the leading commodity of social forestry, which is coffee agroforestry, has not had a significant impact on the welfare of farmers. In addition, the related parties in the agroforestry coffee trade system have not been optimally involved in realizing the independence of the Forest Farmer Group (KTH), especially in managing their businesses. This study aimed to identify and analyze these problems, so as to provide alternative solutions in improving the governance of agroforestry coffee businesses in West Java Province, based on the pentahelix model of collaborative governance. The researchers sought to identify the inhibiting and supporting factors of collaboration as well as the role of stakeholders, so that a more effective collaboration model could be formed. This study used qualitative methods with a descriptive participatory approach. Data were collected through in-depth interviews, field reviews and document analysis. According to the findings, to collaborate in establishing governance institutions for the coffee agroforestry trade in West Java, the government is expected to involve the private sector, academia/universities, civil society/NGOs and the mass media. Each stakeholder has a key role in synergizing their duties, functions and authorities. It was identified that the main keys to collaborative governance are effective communication, optimal multi-stakeholder participation and strong leadership. The interaction between the pentahelix stakeholders can be used as a collaborative governance model in building agroforestry coffee business governance institutions in West Java Province, which can then be replicated throughout Indonesia, and become an alternative policy in developing social forestry business management in the future. Keywords: social forestry, collaborative governance, pentahelix stakeholder, agroforestry coffee